Implications of a electroweak triplet scalar leptoquark on the ultra-high energy neutrino events at IceCube - Mileo, Nicolás Ismael (2016)
We study the production of scalar leptoquarks at IceCube, in particular, a particle transforming as a triplet under the weak interaction. The existence of electroweak-triplet scalars is highly motivated by models of grand unification and also within radiative seesaw models for neutrino mass generation. In our framework, we extend the Standard Model by a single colored electroweak-triplet scalar leptoquark and analyze its implications on the excess of ultra-high energy neutrino events observed by the IceCube collaboration. We consider only couplings between the leptoquark to first generation of quarks and first and second generations of leptons, and carry out a statistical analysis to determine the parameters that best describe the IceCube data as well as set 95% CL upper bounds. We analyze whether this study is still consistent with most up-to-date LHC data and various low energy observables.